ASSESSMENT OF THE CORPORATE GOVERNANCE SYSTEM: NATIONAL AND INTERNATIONAL RATINGS - Yoqubxonova Feruza; Xaydarov Xaydar O'tkirovich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. In today’s rapidly changing global economy, corporate governance has emerged as a key factor determining the sustainability, transparency, and competitiveness of companies. This thesis explores how corporate governance systems are assessed both nationally and internationally through various rating models, indicators, and benchmarks. It examines how these ratings reflect not only a company’s internal management culture and ethical standards but also its alignment with international norms such as the OECD Principles of Corporate Governance and the World Bank’s governance indicators.